2015
DOI: 10.3892/ol.2015.3195
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of human glioma cells by tamoxifen is associated with the inhibition of PKC-ι activity in vitro

Abstract: Abstract. The present study aimed to investigate the radiosensitizing effects of tamoxifen (TAM), a non-steroidal anti-estrogen drug, in human glioma A172 and U251 cells in vitro. A colony-forming assay revealed that TAM enhances radiosensitivity in A172 and U251 cells. Treatment with TAM also increased the percentage of apoptotic cells subsequent to ionizing radiation, and increased the expression of apoptotic markers, including cleaved caspase-3 and poly(ADP-ribose) polymerase. Ionizing radiation induced G2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Newton and colleagues [ 65 ] observed an enhanced apoptotic cell death in MCF-7 cells which were treated by a combination of irradiation and ZM182780, a pure anti-estrogen, or tamoxifen. In a more recent study, tamoxifen enhanced the radiosensitivity of human glioma cells by inducing cell apoptosis and sustaining G2/M arrest [ 66 ]. Moreover, fulvestrant, another pure anti-estrogen drug, revealed a positive effect on radiosensitization of ER-positive breast cancer cells by inducing cell cycle arrest and inhibiting proteins involved in DSB repair [ 67 ].…”
Section: The Combination Of Anti-estrogen and Irradiation Therapy mentioning
confidence: 99%
“…Newton and colleagues [ 65 ] observed an enhanced apoptotic cell death in MCF-7 cells which were treated by a combination of irradiation and ZM182780, a pure anti-estrogen, or tamoxifen. In a more recent study, tamoxifen enhanced the radiosensitivity of human glioma cells by inducing cell apoptosis and sustaining G2/M arrest [ 66 ]. Moreover, fulvestrant, another pure anti-estrogen drug, revealed a positive effect on radiosensitization of ER-positive breast cancer cells by inducing cell cycle arrest and inhibiting proteins involved in DSB repair [ 67 ].…”
Section: The Combination Of Anti-estrogen and Irradiation Therapy mentioning
confidence: 99%
“…It increases the number of apoptotic cells which are more radiosensitive than other phases likely due to the increased number of targets. Thus, the final outcome is a positive balance in favor of Tamoxifen concurrently administered with radiotherapy, which is likely to act as a radio-sensitizer [22].…”
Section: Effect Of Tamoxifen On Radiation Effects On Cancer Cellsmentioning
confidence: 99%
“…Several clinical and clinicopathological studies indicated: cytoreductive surgery for testicular tumors, enhanced tumor progression [20], and post-surgical accelerated growth of metastasis in non-small cell lung cancer [22]. Improved survival and relapse following Laparoscopic cholecystectomy compared to open cholecystectomy Table 3.…”
Section: Effect Of Surgery On Cancer Cell Kineticsmentioning
confidence: 99%
“…Previous studies demonstrated that DNA damage could induce tumor cell apoptosis, and that this is associated with protein kinase C (PKC) activation [ 3 7 ] . Furthermore, recent advances in the study of tumors show that PKC iota (PKC-ι) expression is highly upregulated in tumor cells [ 4 , 8 ]. Notably, Yang et al suggested that the in vitro radiosensitizing effects of tamoxifen on glioma cells were partly caused by the inhibition of PKC-ι activity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent advances in the study of tumors show that PKC iota (PKC-ι) expression is highly upregulated in tumor cells [ 4 , 8 ]. Notably, Yang et al suggested that the in vitro radiosensitizing effects of tamoxifen on glioma cells were partly caused by the inhibition of PKC-ι activity [ 4 ]. We also recently demonstrated that X-ray irradiation could lead to inhibition of PKC-ι activity, and that this correlated with the radiosensitivity of the cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%